Regulatory Optimization of Bitcoin as Collateral: Property Classification and Secured Lending Framework in Indonesia - Darmawan, Kevin; Abubakar, Lastuti; Handayani, Tri; Sugiharti, Dewi Kania (Journal of Law, Politic and Humanities, 2025)
The development of financial technology has driven the emergence of digital assets such as Bitcoin, which challenge the conventional legal framework of property law. Although not recognized as legal tender, Bitcoin has been acknowledged as a legal asset by Indonesia's Commodity Futures Trading Regulatory Agency (Bappebti). This study aims to examine the legal status of Bitcoin as collateral in Indonesia’s property law framework, as well as assess the adequacy of current regulations in accommodating this function. This research employs a normative juridical method with a qualitative approach and deductive reasoning. The findings indicate that Bitcoin fulfills the legal criteria of an intangible object and, in theory, can be used as an object of fiduciary security. However, the absence of explicit legal recognition and a digitally integrated collateral registration system has led to legal uncertainty. Although regulations in Indonesia have provided a degree of legality and oversight, systemic institutional integration remains lacking. Therefore, legal reform is needed in the area of digital asset-based collateral, along with the establishment of a comprehensive administrative registration system to ensure the validity of security interests in digital assets